Reinventing the AI-TPACK Frontier: The AI EdDesign Model as a Catalyst for Pedagogical Innovation - Dirgantara Wicaksono; Rinanto (Jurnal Penelitian dan Penilaian Pendidikan, 2025)
Purpose: This study aims to develop and evaluate the efficacy of the AI EdDesign model in addressing the disparities in artificial intelligence literacy and instructional design competencies among Educational Technology students. Design/methodology/approach: The research utilizes a Research and Development (R&D) methodology by adapting the ADDIE development model. Subjects were partitioned into experimental and control groups to observe the intervention's impact. The research instruments comprised an AI-TPACK competency rubric, cognitive performance assessments, and a technology acceptance questionnaire, all of which underwent rigorous expert validation. Findings: The findings indicate that the AI EdDesign model significantly enhances students' needs analysis and instructional design skills compared to conventional methods. The utilization of generative AI-based virtual tutors proved effective in providing instructional scaffolding that stimulates creativity without inducing cognitive dependency. Subjects reported highly positive perceptions of the personalized learning pathways, which were deemed relevant to their individual developmental requirements. Practical implications: This model offers a practical framework for academic institutions to implement AI as a co-design partner, thereby accelerating the mastery of adaptive pedagogical skills for future educators. Originality/value: The novelty of this study lies in the integration of the AI-TPACK framework into a digital platform capable of mitigating risks to students' critical thinking through structured AI feedback mechanisms.   Purpose: Penelitian ini bertujuan mengembangkan dan menguji efektivitas model AI EdDesign untuk mengatasi kesenjangan literasi kecerdasan buatan serta rendahnya kompetensi desain instruksional pada mahasiswa Teknologi Pendidikan. Design/methodology/approach: Penelitian ini menerapkan metode Research and Development (R&D) dengan mengadaptasi model pengembangan ADDIE. Subjek penelitian melibatkan mahasiswa yang dibagi ke dalam kelompok eksperimen dan kelompok kontrol. Instrumen penelitian terdiri dari rubrik kompetensi AI-TPACK, tes kinerja kognitif, dan kuesioner model penerimaan teknologi yang telah melalui proses validasi ahli. Findings: Temuan menunjukkan bahwa model AI EdDesign secara signifikan meningkatkan kemampuan analisis kebutuhan dan keterampilan desain instruksional mahasiswa dibandingkan metode konvensional. Penggunaan tutor virtual berbasis kecerdasan generatif terbukti efektif memberikan bimbingan scaffolding yang meningkatkan kreativitas tanpa menciptakan ketergantungan kognitif. Subjek memberikan respon positif terhadap fitur personalisasi jalur pembelajaran yang dianggap relevan dengan kebutuhan individu. Practical implications: Model ini memberikan panduan praktis bagi institusi pendidikan dalam mengimplementasikan AI sebagai mitra desain, sehingga mempercepat penguasaan keterampilan pedagogis yang adaptif bagi calon pendidik. Originality/value: Kebaruan studi ini terletak pada integrasi kerangka kerja AI-TPACK ke dalam platform digital yang mampu memitigasi risiko penurunan daya kritis mahasiswa melalui mekanisme umpan balik AI yang terstruktur.